Propagation of Aurides odorata and Aurides multiflora Using Varied Growth Media and Culture Containers - Salitxay, Timnoy; SIVILAY, Phisouda; Namsena, Montha; Malichan, Xaiykham; Chanthala, Khammun (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
A study of propagation of Aurides multiflora and Aurides odorata, by the aim of comparing different mixtures and media for germination and survival rate. There were 4 methods: 1: 100% of coconut shell, 2: Coconut shell + charcoal, 3: Coconut shell + charcoal + cow dung and 4: Coconut shell + charcoal + cow dung + second paper. Each method used 50 pots. The results of the cutting of the Aurides odorata (White rose) showed that all 4 methods had the same average shoot growth rate of 1 shoot/pot, but the average height was: Method 2 was the highest at 13.5cm, followed by Method 3 at 9.3cm, and the lowest were Methods 4 and 1 respectively (8.3 cm; 2.15cm). It was found that Methods 1 and 2 had the highest and equal survival rates (95%) and the lowest were Methods 3 and 4 respectively (63.5%; 63%). The results of the cutting of the Aurides multiflora (Eang Phuang Malai) showed that all 4 methods had the same average shoot growth rate of 1 shoot/pot, but the average height was: Method 2 was the highest at 53cm, followed by Method 4 at 50.6cm, and the lowest were Methods 3 and 1 respectively (39.6cm; 34.7cm) and method 1 had a survival rate of up to 99%, followed by method 2 with up to 96% and the lowest were 4 and 3 respectively (94%; 91.5%). The study found that both types of honeysuckle cuttings using different mixtures and containers resulted in a high rate of sprouting as well as a high survival rate, but the method with coconut shell was more appropriate for this type of honeysuckle cutting.